Evaluation of alginate compressed matrices as prolonged drug delivery systems - Giunchedi, Paolo (Springer-Verlag, 2000)
This research investigated the use of sodium alginate for the preparation of hydrophylic matrix tablets intended for prolonged drug release using ketoprofen as a model drug. The matrix tablets were prepared by direct compression using sodium alginate, calcium gluconate, and hydroxypropylmethylcellulose (HPMC) in different combinations and ratios. In vitro release tests and erosion studies of the matrix tablets were carried out in USP phosphate buffer (pH 7.4). Matrices consisting of sodium alginate alone or in combination with 10% and 20% of HPMC give a prolonged drug release at a fairly constant rate. Incorporation of different ratios of calcium gluconate leads to an enhancement of the release rate from the matrices and to the loss of the constant release rate of the drug. Only the matrices containing the highest quantity of HPMC (20%) maintained their capacity to release ketoprofen for a prolonged time.